THE INFLUENCE OF LEADERSHIP AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE - Ira Mutia; Fajar Pasaribu (International Journal of Accounting, Finance and Business, 2023)
The purpose of this study is to determine and analyze the influence of leadership on employee performance, the influence of work discipline on employee performance, the influence of leadership on job satisfaction, the influence of work discipline on job satisfaction, the effect of job satisfaction on employee performance, the influence of leadership on employee performance through job satisfaction, the influence of work discipline on job satisfaction, the influence of work discipline on employee performance through job satisfaction. This study used a causal type using a quantitative approach with a sample of 71 respondents who were permanent employees of Putri Hijau Medan Hospital. The data collection technique uses interviews and a list of statements such as questionnaires and the data analysis technique uses Partial Least Square (SmartPls) to test the seven hypotheses proposed in this study. The results showed that leadership has a significant effect on employee performance, work discipline has a significant effect on employee performance, leadership has a significant effect on job satisfaction, work discipline has a significant effect on job satisfaction, person organization fit has a significant effect on employee performance through job satisfaction (in other words job satisfaction acts as a mediator), work discipline has a significant effect on employee performance through job satisfaction (In other words, job satisfaction acts as a mediator).